Building resilience to body image triggers using brief cognitive training on a mobile application: A randomized controlled trial. (November 2020) - Aboody, Dinur; Siev, Jedidiah; Doron, Guy
Abstract: Objective: Body image disturbance (BID) is common among women, characterized by persistent and distressing appearance dissatisfaction, and linked with eating disorders. Although effective, cognitive behavioral therapy (CBT) delivered by trained professionals is not easily accessible. This randomized trial evaluated the effects of a CBT-based mobile application designed to increase resilience to body image triggers and reduce BID symptoms. Method: A non-clinical sample of women ( N = 90; Mage = 23.52) was randomized to use the mobile application for approximately 4 min of daily exercises for two weeks or to a control condition. Body image was measured at baseline, immediately after two weeks of mobile application use, and at 1-month follow-up. To examine whether using the application was associated with increased resilience to common BID triggers, participants completed an Instagram exposure resilience task upon completion and at 1-month follow-up. Results: Relative to those in the control condition, participants who used the application demonstrated increased resiliency and reduced BID symptoms. Theses effects were medium-to-large and were maintained at 1-month follow-up. Conclusion: These results underscore the potential usefulness of brief, low-intensity, portable interventions in reducing BID symptoms and in increasing resilience to thin-ideal body messages often portrayed on social media. Highlights: Body image disturbance (BID) is a common condition among women. We investigated an accessible mobile application for BID. Application use was linked with decreased BID and increased body appreciation. Users of the app showed increased resilience on an Instagram exposure task.